SNP-based diagnosis of robertsonian translocation 1;29 in Italian cattle breeds: frequency estimation and efficient detection - A. Bionda; M. Cortellari; A. Cesarani; F. Sbarra; A. Quaglia; L. Liotta; P. Parma; P. Crepaldi (Italian Journal of Animal Science)
Robertsonian translocation 1;29 (rob(1;29)) is the most widespread chromosomal aberration in cattle, known to cause fertility impairment in heterozygous carriers. While karyological screening programs exist for some breeds, the analysis of SNP data has proven to be a faster and more cost-effective method to identify carriers. In this study, we analysed SNP data from 1938 individuals across 11 Italian cattle breeds, routinely collected by four breeders’ associations, to screen for the rob(1;29) translocation. We focused on the first six Mb of chromosome 29, using principal component analysis and partitioning methods to identify the smallest subset of SNPs that could reliably detect carriers. Additionally, we investigated linkage disequilibrium (LD) between chromosomes 1 and 29 in rob(1;29) carriers. The frequency of rob(1;29) carriers in five beef breeds of Podolian origin was consistent with previous reports. No carriers were found in the Piedmontese or Pezzata Rossa Italiana breeds. 2% of Modicana and Bruna Italiana, and 1% of Pezzata Rossa d’Oropa subjects were carriers. Moreover, 40% of Cinisara individuals carried rob(1;29), including 4% who were homozygous. Depending on the array used, we identified one to three SNPs that, alone, could distinguish between carriers and wild type individuals. LD analysis showed no significant hotspots between BTA 1 and 29, but the average linkage was higher in carriers. Our findings confirm that a small SNP set from this region can effectively detect rob(1;29) carriers, supporting its inclusion in routine genotyping panels for broader and more efficient screening across cattle populations.